2022
DOI: 10.1002/cam4.4845
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic adenovirus H101 ameliorate the efficacy of anti‐PD‐1 monotherapy in colorectal cancer

Abstract: Background Immune checkpoint blockade therapy with anti‐programmed cell death (PD)‐1 antibodies provides therapeutic effect for many patients of various cancers but remains inadequate in colorectal cancer (CRC) patients. The present study aims to assess the efficacy of oncolytic adenovirus (OncoAd) in enhancing the anti‐PD‐1 treatment of CRC. Methods The estimating relative subsets of RNA transcripts algorithm was used for estimating the infiltrated immune cells in melanoma and CRC tissues. The efficacy of Onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For Ad therapies, the liver is a considerable sink for Ad that reach the systemic circulation, which may diminish therapeutic efficacy [ 33 , 34 ]. Oncolytic viruses are commonly injected intratumorally to achieve high levels in the injected tumor(s) while minimizing off-target activity [ 55 , 56 , 57 ]. With CAR-negative CT26 tumors, intratumoral injection nevertheless resulted in poor transduction of the tumor and primarily led to off-target transduction in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…For Ad therapies, the liver is a considerable sink for Ad that reach the systemic circulation, which may diminish therapeutic efficacy [ 33 , 34 ]. Oncolytic viruses are commonly injected intratumorally to achieve high levels in the injected tumor(s) while minimizing off-target activity [ 55 , 56 , 57 ]. With CAR-negative CT26 tumors, intratumoral injection nevertheless resulted in poor transduction of the tumor and primarily led to off-target transduction in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human adenovirus type 5 (H101, also known as Oncorine), a genetically modified oncolytic adenovirus, has demonstrated clinical efficacy for treating various malignancies. 9–11 Huang et al, 12 confirmed that H101 ameliorated the efficacy of anti-PD-1 monotherapy in CRC. Herein, this report details a case of substantial abdominal lymph node metastasis, measuring 12 cm in diameter, following CRC surgery.…”
Section: Introductionmentioning
confidence: 91%
“…Another study using an E1A delta24 OAd expressing a modified version of PD-1 (Ad-CAB) demonstrated excellent immune cell killing of tumor cell both with small cell lung carcinoma [ 32 ]. Combination of H101 with anti-PD-1 therapy was shown to enhance anti-tumor response in murine colorectal cancer [ 33 ].…”
Section: Combining Oncolytic Adenovirus With Immune Checkpoint Inhibi...mentioning
confidence: 99%